Self-organizing cognitive model synthesis with deep learning support - Raikov, A; Ermakov, A; Merkulov, A (International Journal of Engineering and Technology, 2018)
Cognitive models are created by experts and the process takes a lot of time. Furthermore, the result of expert work needs to be verified especially in cases when experts do not have complete information and cannot understand the problem situation quickly. As was previously shown cognitive modelsâ€™ factors and their mutual relationships could be verified with applying Big Data analysis technology. This paper addresses the issue of automated cognitive models synthesis on the base of authorâ€™s convergent methodology, artificial intelligence and deep learning technology.Â